1969
DOI: 10.1152/ajplegacy.1969.216.4.898
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of increased serum osmolality on left ventricular performance

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
2

Year Published

1972
1972
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(32 citation statements)
references
References 0 publications
3
26
1
2
Order By: Relevance
“…In contrast to results in intact skeletal muscles (7,8) that show a depression of mechanical performance when the osmolality of the external medium is increased, the present study confirms the known potentiating effect of a moderately elevated osmolality in heart muscle at lower Ca concentrations (9,13,14). This potentiation could be explained by slight cellular dehydration with a concomitant increase in activating intracellular Ca concentrations either directly (9) or indirectly through a slight increase in intracellular sodium (Na) concentration that enhances Ca influx (15).…”
Section: Discussionsupporting
confidence: 70%
“…In contrast to results in intact skeletal muscles (7,8) that show a depression of mechanical performance when the osmolality of the external medium is increased, the present study confirms the known potentiating effect of a moderately elevated osmolality in heart muscle at lower Ca concentrations (9,13,14). This potentiation could be explained by slight cellular dehydration with a concomitant increase in activating intracellular Ca concentrations either directly (9) or indirectly through a slight increase in intracellular sodium (Na) concentration that enhances Ca influx (15).…”
Section: Discussionsupporting
confidence: 70%
“…We are not aware of published clinical data to support such speculation. However, animal studies indicate that cardiac contractility in vivo can be enhanced by similar increases in plasma osmolarities induced by infusion of sucrose (Wildenthal, Mierzwiak & Mitchell, 1969) or mannitol (Atkins, Wildenthal & Horowitz, 1973). This enhancement of contractility is sustained for at least 30 min after the increase in osmolarity.…”
Section: Possible Implications For In Vivo Effects Of Hyperosmolaritymentioning
confidence: 99%
“…Specifically, is some of the positive inotropic effect of mannitol on ischemic myocardium independent of its influence on blood flow? Previous investigators have demonstrated that certain hyperosmolar agents, including mannitol, increase dP/dt in the whole heart and developed tension and its first derivative in the papillary muscle in welloxygenated systems within a cetrain osmolality range (14)(15)(16). The present data which include the results of experiments done with autonomic blockade, and the recent study by Atkins, Wildenthal, and Horowitz (17) suggest that this increase in contractility is due to a direct effect on the myocardium rather than a neurohumoral response to stimulation of a peripheral receptor (18).…”
Section: Introductionmentioning
confidence: 99%